Screening for hepatocellular carcinoma: patient selection and perspectives - Fateen, Waleed; Ryder, Stephen (Dove Medical Press, 2017)
Hepatocellular carcinoma (HCC) develops on the background of liver cirrhosis often from multiple, simultaneous factors. The diagnosis of a single small HCC comes with good prognosis and provides a potential for cure. In contrast, the diagnosis of multifocal, large HCC has high mortality and poor prognosis. Unfortunately, the majority of HCC is diagnosed at such late stages. A surveillance program endorsed by regional liver societies involves six-monthly ultrasound surveillance of at-risk patients. This had been in action for the last two decades. It has led to marked increase in the proportion of patients presenting with small unifocal nodules found on surveillance. The development of tools to enhance our ability in optimizing available surveillance is likely to improve the prognosis of patients with HCC. In this review, we discuss the difficulties in utilizing HCC surveillance and possible means of improvement.